ANALISIS EFISIENSI TEKNIS PENERAPAN PENGENDALIAN HAMA TERPADU (PPHT) SKALA KAWASAN PADA TANAMAN PADI (Oryza sativa L) DI PADEMAWU BARAT, PAMEKASAN - Mohammad Shoimus Sholeh; Kustiawati Ningsih; Henny Susilawati (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2019)
The application of management integrated pest scale area is a solution in the problems of organisms bully plant scale area and the management of synergism strategy pest by farmers in the same region so contribute real measurable against the program of farming production rice. The application of management integrated plant scale must be efficient area technically in order to get rice production maximum. The farmer can improve production and rice productivity by using the production factors efficiently. The objectives of the research are analyze the production factors which affect the rice farming and analyze of technical efficiency of rice farming. The stochastic frontier is used in this research to analyze technical efficiency. From the frontier analysis will be obtained the factors which give impact to the rice farming organic fertilizer, chemical fertilizers, botanical pesticides and chemical pesticides. The average of technical efficiency is 0,93, it means the farmers are attains 93% of production from the potential production of rices and there is still 7% to improve rice production. Within the value of average technical efficiency is 0,93 will be obtained the income of this farming is Rp. 22.332.779,- per hectare in once growing season. Keywords: intregeted pest management, factor of productions, stochastic frontier, efficiency.